2022
DOI: 10.1371/journal.ppat.1010726
|View full text |Cite
|
Sign up to set email alerts
|

HIV infected CD4+ T cell clones are more stable than uninfected clones during long-term antiretroviral therapy

Abstract: Although combination antiretroviral therapy (ART) blocks HIV replication, it is not curative because infected CD4+ T cells that carry intact, infectious proviruses persist. Understanding the behavior of clones of infected T cells is important for understanding the stability of the reservoir; however, the stabilities of clones of infected T cells in persons on long-term ART are not well defined. We determined the relative stabilities of clones of infected and uninfected CD4+ T cells over time intervals of one t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Thus the HIV cure field may be biased towards results implying that antigen-driven proliferation provides the dominant stimulus for the persistence of the HIV latent reservoir. We show that the clonality and the longitudinal dynamics of non-dominant HIV-infected clones – the ‘tail’ or the second slope of the clonality distribution -have not yet been characterized ( Figure 3F ), although non-dominant clones probably make up the majority of HIV-infected cells in humans 34,35,38 . Because of this gap in knowledge, it remains unknown whether homeostatic proliferation, less frequent or intense antigen exposure, or other forces underlie the persistence of the reservoir in non-dominant clones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus the HIV cure field may be biased towards results implying that antigen-driven proliferation provides the dominant stimulus for the persistence of the HIV latent reservoir. We show that the clonality and the longitudinal dynamics of non-dominant HIV-infected clones – the ‘tail’ or the second slope of the clonality distribution -have not yet been characterized ( Figure 3F ), although non-dominant clones probably make up the majority of HIV-infected cells in humans 34,35,38 . Because of this gap in knowledge, it remains unknown whether homeostatic proliferation, less frequent or intense antigen exposure, or other forces underlie the persistence of the reservoir in non-dominant clones.…”
Section: Discussionmentioning
confidence: 99%
“…However, the labor-intensive nature of provirus sequencing and the rarity of HIV-infected cells in single cell RNA sequencing approaches make it prohibitively time-consuming or expensive to reach HIV provirus sampling depths much beyond 100. One group has directly compared HIV integration site datasets – which do not distinguish intact from defective proviruses -on the order of 1000+ per sample to mCD4 TCRβ repertoires and found that the largest HIV-infected clones are more stable than randomly-chosen mCD4+ T cell clones of the same size 35 . One plausible explanation for this is that the largest HIV-infected clones are biologically more similar to the largest randomly-chosen mCD4+ T cell clones instead of the mid-sized clones with which they were compared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these expanded cell clones carry replication-competent (intact) proviruses and comprise the HIV reservoir that leads to viral rebound if cART is stopped. Cell clones that carry defective or intact proviruses can wax and wane over time ( 11 - 13 ), although most are highly stable ( 14 ). Some clones of infected cells produce enough virus to be detected in the blood by standard plasma HIV RNA assays despite effective cART ( 11 , 15 ).…”
Section: Introductionmentioning
confidence: 99%